Peningkatan Pertumbuhan dan Produksi Beberapa Varietas Tanaman Zea mays saccharata Sturt. Melalui Pemberian Pupuk Organik Vermikompos - Nurbaiti Amir; Berliana Palmasari; R Iin Siti Aminah; Ika Paridawati (Seminar Nasional Lahan Suboptimal, 2021)
Amir N, Palmasari B, Aminah RIS, Paridawati I. 2021. Increased growth and production of several crop varieties zea mays saccharata sturt. by giving vermicompost organic fertilizer In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 186-193.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The aim of this study was to determine the varieties and doses of vermicompost organic fertilizer that had the best effect on the growth and production of sweet corn (Zea mays saccharata Sturt.). This research has been carried out on land owned by farmers located in Pasir Putih Village, Talang Kelapa District, Banyuasin Regency, South Sumatra. This research was conducted from September to December 2020. This study used a Split-plot design consisting of 9 treatment combinations and 3 replications. As the main plot treatment, Varieties Type (V): V1 = Bonanza ; V2 = Sweet Boy ; V3 = Sweet Lady and subplot treatment Amount of Vermicompost Organic Fertilizer (K): K1 = 1 ton/ha; K2 = 3 tons/ha ; K3 = 5 tons/ha. Observational variables in this study included: plant height (cm), number of leaves (strands), weight of cobs per plant (g) and weight of cobs per plot (kg). The results showed that the tabulation of the combination of Bonanza variety and the dose of organic fertilizer vermicompost 5 tons/ha gave the highest growth and production of sweet corn plants with a production of 2.43 kg/plot (3,24 ton/ha).